When do managers highlight their effective tax rate? - Vanessa Flagmeier; Jens Müller; Caren Sureth-Sloane (Arbeitskreis Quantitative Steuerlehre (arqus), 2017)
We examine the disclosure of GAAP effective tax rate (ETR) information in firms' financial statements. Applying the theoretical underpinnings of Wagenhofer (1990) to a tax setting, we argue that firms face a tradeoff in their GAAP ETR disclosure decision. On the one hand, firms have incentives to increase GAAP ETR disclosure if the ratio has a condition that is favorable from an investor's perspective, expecting positive capital market reactions. On the other hand, the disclosure might draw tax auditors' and public attention to the GAAP ETR and result in proprietary costs in terms of additional tax payments or reputational damages. We empirically test the disclosure behavior by examining the relation between disclosure intensity and five different measures of favorable GAAP ETR conditions. First, we provide evidence that the annual report section in which most of the firms disclose GAAP ETR information is the management report, indicating that firms assign considerable relevance to the ratio. Second, we find a higher disclosure intensity if the GAAP ETR has a favorable condition, i.e. is decreasing or near the average ratio of firms in the same industry or size group. We do not find a significant relation to the disclosure level for smooth GAAP ETRs. Our findings indicate that firms assess the benefits of providing the favorable GAAP ETR information to be higher than the related costs. Documenting firms' GAAP ETR reporting behavior, we contribute to the tax disclosure literature by providing insights into possible disclosure incentives. Further, our results could increase awareness among investors to have a second look at the GAAP ETR if the disclosure intensity with respect to the ratio is low.
Keywords: 330; Effective Tax Rate; Disclosure; Proprietary Costs